Differences in childbearing by time frame of fertility intention. A study using survey and register data from Norway - Lars Dommermuth; Jane Klobas; Trude Lappegård (Statistics Norway, Research Department, 2014)
This paper focuses on the realization of positive fertility intentions with different time frames. The analyses are based on a unique combination of survey data and information from Norwegian administrative registers on childbearing in the years following the complete selected sample. Guided by the theoretical and empirical framework of the Theory of Planned Behavior (TPB), the results suggest that a fertility intention's time frame is relevant for childbearing behaviour, but the patterns are somewhat different for respondents who were childless at the time of the interview compared to those who already had children. Overall, childless respondents were less likely to realize their fertility intentions than parents. Following the TPB, childless individuals may underestimate the difficulty of acting on their intentions and therefore have more difficulty realizing their intentions, versus parents who take into account their ability to manage another child. The results also show that childless individuals with an immediate fertility intention are more likely to succeed than those with a longerterm intention. Likewise, parents with an immediate fertility intention are more likely to realize their intention during the two first years after the interview, but after four years the childbearing rate was higher among those with longer-term fertility intentions.
Keywords: N34; Z10; Z13; 330; Childbearing; Fertility intentions; Time frame of fertility intentions; Realization of fertility intentions; Fertility; Theory of Planned Behavior; Norway; GGS; Register data